Exploring Cortical Plasticity and Oscillatory Brain Dynamics via Transcranial Magnetic Stimulation and Resting-State Electroencephalogram - Noh, NA (Univ Sains Malaysia, Sch Medical Sciences, 2024)
Transcranial magnetic stimulation (TMS) is a non-invasive, non-pharmacological technique that is able to modulate cortical activity beyond the stimulation period. The residual aftereffects are akin to the plasticity mechanism of the brain and suggest the potential use of TMS for therapy. For years, TMS has been shown to transiently improve symptoms of neuropsychiatric disorders, but the underlying neural correlates remain elusive. Recently, there is evidence that altered connectivity of brain network dynamics is the mechanism underlying symptoms of various neuropsychiatric illnesses. By combining TMS and electroencephalography (EEG), the functional connectivity patterns among brain regions, and the causal link between function or behaviour and a specific brain region can be determined. Nonetheless, the brain network connectivity are highly complex and involve the dynamics interplay among multitude of brain regions. In this review article, we present previous TMS-EEG co-registration studies, which explore the functional connectivity patterns of human cerebral cortex. We argue the possibilities of neural correlates of long-term potentiation/depression (LTP-/LTD)-like mechanisms of synaptic plasticity that drive the TMS aftereffects as shown by the dissociation between EEG and motor evoked potentials (MEP) cortical output. Here, we also explore alternative explanations that drive the EEG oscillatory modulations post TMS. The precise knowledge of the neurophysiological mechanisms underlying TMS will help characterise disturbances in oscillatory patterns, and the altered functional connectivity in neuropsychiatric illnesses.